Academic trip to Kuala Lumpur - Austin, Anastasia Sasha (Universiti Teknologi MARA, Sarawak, 2015)
The main objective of this academic trip was to give an opportunity to the students to be exposed to the institutions covered in their course, and to be there to ‘get first hand information’ from the respective management of the institutions mentioned. Apart from that, the purpose of the trip was to fulfil the requirements of the course, “Issues and Ethics in Finance” taken by these students.